Three new Nearctic genera of oak cynipid gall wasps (Hymenoptera: Cynipidae: Cynipini): Burnettweldia Pujade-Villar, Melika & Nicholls, Nichollsiella Melika, Pujade-Villar & Stone, Disholandricus Melika, Pujade-Villar & Nicholls; and re-establishment of the genus Paracraspis Weld - Melika, George; Pujade-Villar, Juli; Nicholls, James A.; Cuesta-Porta, Victor; Cooke-Mcewen, Crystal; Stone, Graham N. (Zootaxa, 2021)
We describe three new genera of cynipid oak gall wasps from the Nearctic: Burnettweldia Pujade-Villar, Melika & Nicholls, gen. nov., Nichollsiella Melika, Pujade-Villar & Stone, gen. nov., and Disholandricus Melika, Pujade-Villar & Nicholls, gen. nov. (Hymenoptera: Cynipidae: Cynipini). Burnettweldia includes five species, B. californicordazi Cuesta-Porta, Melika & Pujade-Villar, sp. nov., B. conalis (Weld), comb. nov., B. corallina (Bassett), comb. nov., B. plumbella (Kinsey), comb. nov., B. washingtonensis (Gillette), comb. nov.. Nichollsiella includes three species, N. arizonica (Cockerell), comb. nov., N. sulcata (Ashmead), comb. nov., and N. puigi Melika, Cuesta-Porta & Pujade-Villar, sp. nov.. Disholandricus includes four species, D. chrysolepidis (Ashmead), comb. nov., D. lasius (Ashmead), comb. nov., D. reniformis (McCracken & Egbert), comb. nov., D. truckeensis (Ashmead), comb. nov. The genus Paracraspis Weld, comb. rev. is re-established with three species, P. guadaloupensis (Fullaway), P. insolens (Weld), and P. patelloides (Trotter). Descriptions, re-descriptions, diagnoses, keys to genera and species are given, including data on DNA sequences, biology, phenology and distribution.